Den Tigerfrauen wachsen Flügel . Tigerwomen Grow Wings - Treut, Monika (Treut, Monika, 2004)
Duration: 01:23:00 A portrait of three women from different generations. Opera singer Hsieh Yueh Hsia experienced the Japanese occupation and the takeover of Taiwan by the National Chinese forces; she believes in traditional values and a strict hierarchy within the family. The next generation have seen a shift away from traditional female roles in Taiwanese society towards the idea of the modern woman, struggling for independence and equality. Writer Li Ang experienced the military dictatorship’s repressive value system; she also saw, as a young adult, the country’s transition to democracy. Young film director Chen Yin-jung, however, is a firm believer in modernity and globalization. This film is not only about the individual biographies of three women; it also aims to depict Taiwanese society during the heady days of transition from one political system to another.